Spinal cord vascular degeneration impairs duloxetine penetration - Da Vitoria Lobo, M. E; Madden, R; Liddell, S; Hirashima, M; Hulse, R. P (Frontiers in Pain Research, 2023)
Introduction Chronic pain is a prevalent physically debilitating health-related morbidity. Frontline analgesics are inadequate, providing only partial pain relief in only a proportion of the patient cohort. Here, we explore whether alterations in spinal cord vascular perfusion are a factor in reducing the analgesic capability of the noradrenaline reuptake inhibitor, duloxetine. Method An established rodent model of spinal cord vascular degeneration was used. Endothelial-specific vascular endothelial growth factor receptor 2 knockout mouse was induced via hydroxytamoxifen administered via intrathecal injection. Duloxetine was administered via intraperitoneal injection, and nociceptive behavioural testing was performed in both WT and VEGFR2KO mice. LC-MS/MS was performed to explore the accumulation of duloxetine in the spinal cord in WT and VEGFR2KO mice. Results Spinal cord vascular degeneration leads to heat hypersensitivity and a decline in capillary perfusion. The integrity of noradrenergic projections (dopa - hydroxylase labelled) in the dorsal horn remained unaltered in WT and VEGFR2KO mice. There was an association between dorsal horn blood flow with the abundance of accumulated duloxetine in the spinal cord and analgesic capacity. In VEGFR2KO mice, the abundance of duloxetine in the lumbar spinal cord was reduced and was correlated with reduced anti-nociceptive capability of duloxetine. Discussion Here, we show that an impaired vascular network in the spinal cord impairs the anti-nociceptive action of duloxetine. This highlights that the spinal cord vascular network is crucial to maintaining the efficacy of analgesics to provide pain relief.